The World Health Organization World Mental Health International College Student initiative: An overview. Issue 2 (6th January 2019) - Cuijpers, Pim; Auerbach, Randy P.; Benjet, Corina; Bruffaerts, Ronny; Ebert, David; Karyotaki, Eirini; Kessler, Ronald C.
Abstract: Objectives: The college years are a developmentally crucial period and a peak age for the onset of mental disorders. Methods: The World Health Organization World Mental Health International College Student (WMH‐ICS) initiative is aimed at developing and implementing a system for improving prevention and early interventions for mental health problems among college students. Results: The initiative consists of three core elements. The first element is a web‐based survey to assess the magnitude and nature of emotional problems, the effects of these problems on students' functioning, and barriers to seeking treatment. All first‐year students in participating colleges are invited to participate, and we plan to expand the survey to all students in the future. The second element is an infrastructure to test internet‐based interventions aimed at the prevention and early intervention in mental health problems. Participating colleges can develop and test internet‐based interventions in randomized trials. The first pilot tests on such interventions now been done. The third element is the dissemination and continuous quality improvement monitoring of the evidence‐based interventions developed in WMH‐ICS. Conclusions: By addressing these three core elements, the WMH‐ICS aims to integrate epidemiological and clinical research to offer scalable and effective evidence‐based interventions for mental health problems at a critical life course stage.